La mujer liberada de la dominación masculina en Algunas mentiras y otros cuentos de Daniel Gonzales - Bañez Gamarra, Eli Jeferson (2021)
This paper analyzes the book Algunas mentiras y otros cuentos by Da-niel Gonzales Rosales, specifically the first four stories of the first sec-tion and all the micro-stories of the second section. This is due to the fact that the stories maintain thematic unity and intentionality. Accor-ding to our hypothesis, in the book the female characters show atti-tudes of resistance and even subvert the symbolic violence, until they achieve their liberation. In this way, the ideas of male domination and symbolic violence, according to Pierre Bourdieu's proposals, are con-trasted with the resistance and subversion that the female characters manifest.